Pengaruh Terapi Rendam Kaki dengan Air Hangat dan Garam terhadap Tekanan Darah pada Penderita Hipertensi di Desa Jompo Kulon Kecamatan Sokaraja - Nabila Fikrah Cahya Suwarno; Mariah Ulfah; Suci Khasanah (Jurnal Kesehatan Amanah, 2026)
Hypertension is a public health problem whose prevalence continues to increase and carries the risk of causing various serious complications if not properly managed. In addition to pharmacological therapy, non-pharmacological therapy is needed as a supporting effort in controlling blood pressure, one of which is foot soak therapy with warm water and salt. This study aims to determine the effect of foot soak therapy with warm water and salt on blood pressure in hypertension sufferers in Jompo Kulon Village, Sokaraja District. This research method is Pre-experimental with a one-group pretest posttest design. The sampling technique used Purposive sampling of 82 respondents with hypertension. Data was collected by measuring blood pressure before and after foot soak therapy with warm water and salt. The results showed that hypertension sufferers were experienced by respondents aged over 61 years as many as 53 people (64.6%), female as many as 65 people (79.3%). With an average blood pressure before giving foot soak therapy with warm water and salt of 151/88 mmHg, after giving therapy respondents had an average blood pressure of 136/81 mmHg. The results of the Wilcoxon statistical test showed that there was a decrease in blood pressure in the form of systolic blood pressure in 81 respondents and diastolic blood pressure in 68 respondents with a p-value of 0.000 <0.05, which means that there was an effect of providing foot soak therapy with warm water and salt.